Population shift of binding pocket size and dynamic correlation analysis shed new light on the anticooperative mechanism of PII protein. Issue 6 (23rd November 2013) - Ma, Cheng‐Wei; Lüddecke, Jan; Forchhammer, Karl; Zeng, An‐Ping
Abstract PII protein is one of the largest families of signal transduction proteins in archaea, bacteria, and plants, controlling key processes of nitrogen assimilation. An intriguing characteristic for many PII proteins is that the three ligand binding sites exhibit anticooperative allosteric regulation. In this work, PII protein from Synechococcus elongatus, a model for cyanobacteria and plant PII proteins, is utilized to reveal the anticooperative mechanism upon binding of 2‐oxoglutarate (2‐OG). To this end, a method is proposed to define the binding pocket size by identifying residues that contribute greatly to the binding of 2‐OG. It is found that the anticooperativity is realized through population shift of the binding pocket size in an asymmetric manner. Furthermore, a new algorithm based on the dynamic correlation analysis is developed and utilized to discover residues that mediate the anticooperative process with high probability. It is surprising to find that the T‐loop, which is believed to be responsible for mediating the binding of PII with its target proteins, also takes part in the intersubunit signal transduction process. Experimental results of PII variants further confirmed the influence of T‐loop on the anticooperative regulation, especially on binding of the third 2‐OG. These discoveries extend our understanding of the PII T‐loop from being essential in versatile binding of target protein to signal‐mediating in the anticooperative allosteric regulation. Proteins 2014; 82:1048–1059. © 2013 The Authors. Proteins: Structure, Function, and Bioinformatics Published by Wiley Periodicals, Inc.